PTU-306 The efficacy of mrcp in suspected gallstone disease when the biliary tree is normal on previous imaging. (22nd June 2015) - Graby, J; Goldman, A; McPhail, M; Vadwhana, B; Lewis, M; Ramsey, C; Monahan, K
Abstract : Introduction: Magnetic Resonance Cholangiopancreatography (MRCP) is increasingly used in the diagnosis of biliary abnormalities, particularly in stone disease. 1 However initial studies into its role in the absence of a dilated biliary system on initial imaging have demonstrated a low diagnostic yield. 2 The aim of this study was to further assess the role of MRCP when the biliary tree is non-dilated on index imaging. The factors associated with diagnostic yield in this setting are unclear. Method: We performed a retrospective observational study of consecutive MRCP studies (n = 375) performed between October 2010 and June 2013 at West Middlesex University Hospital using electronic medical records. All MRCPs were reported by a consultant gastrointestinal radiologist. MRCP findings were correlated with the presence of dilated or non-dilated biliary tree on initial imaging (USS/CT), jaundice (bilirubin > 21 μmol/L), transaminitis (alanine transaminase >45 iu/L, aspartate transaminase >34 iu/L), raised alkaline phosphatase (>120 iu/L) and abdominal pain, and demographics including age and gender. Multivariate logistic regression analysis was performed using SPSS software. Results: The study included 243 female and 132 male patients with a mean age of 62 (range 20–101) years. There were 153 patients with biochemical jaundice, 246 with a dilated biliary system and 129 with a non-dilated system. The sensitivity of MRCP was 81%, with a specificity of 80%. Multivariate analysis identified that age (p = 0.0253), the presence of jaundice (p = 0.0247), and abnormal index imaging (p = 0.0003), are statistically significant predictors of the finding of biliary tree abnormalities on subsequent MRCP (see attached Table 1 ). The c statistic for the multivariate analysis was only moderately high at 0.665 (95% CI 0.614–0.712, p < 0.001). Conclusion: These data confirm there is a low diagnostic yield of MRCP in the absence of dilated biliary system on previous USS/CT. We propose that there should be a specific rationale for performing MRCP when initial imaging is normal, especially when the bilirubin is normal. Other clinical indices such as pain or abnormal liver chemistry (other than hyper-bilirubinaemia) are not independently predictive of positive finding on MRCP in our analysis. Disclosure of interest: None Declared. References: Shanmugam V, et al . Is magnetic resonance cholangiopancreatography the new gold standard in biliary imaging? Br J Radiol . 2005;78:888–893 Vadwhana B, et al . Is MRCP a useful investigation where the biliary tree is normal on previous imaging? Gut 2013;62 (Suppl 1):A210